Review of Ogden, Thomas H. (2025). ‘Inventing Psychoanalysis with Each Patient’. International Journal of Psychoanalysis, 106, 3, 473–488. https://doi.org/10.1080/00207578.2024.2447708 - Mark Winborn (Journal of Analytical Psychology, 2026)
Abstract Thomas Ogden has been at the forefront of creative, original analytic thought and practice for more than 40 years. Ogden’s agenda is clearly stated in the title of his paper, i.e., that the analyst should endeavour to ‘invent’ a new approach to psychoanalysis with every patient. However, Ogden is not advocating for an ‘anything goes’ approach to this process of invention. Before we can ‘invent’ a new psychoanalysis with each patient, Ogden suggests that the analyst should come to a self‐understanding of: What does it mean to become a psychoanalyst? What is definitive of psychoanalytic thinking? What is distinctive practising psychoanalysis? We could consider “Inventing a New Psychoanalysis with Each Patient” a succinct distillation of his previous reflections on what it means to be a psychoanalyst and to ‘practise’ psychoanalysis.